Patrones culturales de los padres de familia influyen en el maltrato infantil del aa.hh. tambo real del distrito de guadalupe. 2015 - Sanchez Chicchon, Clara Estrella (2016)
This research aims to demonstrate the reasons giving rise to the abuse in children and adolescents and the consequences that could have I short-term and long-term, since we know that in our society there are parents who want to give a good education to their children disciplining them in an improper manner or in many cases the father does not comply any disciplinary purposes rather, serves as escape to your own anger, feelings, frustration and misery. The importance of this research focuses on the number of complaints, which every year are presented by this fact. In our society, and nowadays is often given all the types of abuse that exist and this makes it difficult and hinders the development of the child and the child in all its aspect, which through this research hope that it can raise awareness in every one of the people of the society of our country, which in one way or another have resorted in the mistreatment of children , in the same way, are children, the beneficiaries.